Delaminating Vanadium Carbides for Zinc‐Ion Storage: Hydrate Precipitation and H+/Zn2+ Co‐Action Mechanism. Issue 12 (29th August 2019) - Wang, Changda; Wei, Shiqiang; Chen, Shuangming; Cao, Dengfeng; Song, Li
Abstract: Aqueous zinc (Zn) ion energy devices have demonstrated remarkable significance as a substitute of their lithium counterparts. Developing cheap and nontoxic electrode active materials is crucial for maximizing the storage of Zn ions. As a new star of 2D materials, MXenes can pose unique layered structure and abundant surface chemistry, largely benefiting the surface storage of ions. Herein, carbon nanotube (CNT) delaminated V2 C MXene (DV2 C@CNT) has been demonstrated, as a promising electrode for high‐performance Zn‐ion supercapacitor. The as‐prepared DV2 C@CNT electrodes display favorable electrochemical activity with reversible proton (H + ) and Zn ion (Zn 2+ ) co‐insertion/extraction process in ZnSO4 solutions. Due to the superior conductive network formed by CNT, the delaminated MXene exhibit a high specific capacity of 190.2 F g −1 at 0.5 A g −1 with excellent rate performance and durability. More interestingly, the characterizations clearly reveal that zinc hydroxide sulfate hydrate nanoflakes can immediately precipitate onto the electrode even at the initial assembly process, which can be ascribed to the spontaneous formation of the electrostatic field in the primary battery. The operando X‐ray absorption spectroscopic measurements further confirm the dynamic hydrate precipitation during charging/discharging cycles, offering a better understanding of energy storage mechanism in Zn‐ion devices with MXene electrodes. Abstract : Porous delaminated V2 C MXene and carbon nanotube film electrodes are prepared for hybrid zinc‐ion device. The proton and zinc‐ion co‐insertion process is clearly verified, proving the H + /Zn 2+ co‐action mechanism. Operando X‐ray absorption fine structure reveals the immediate precipitation of (Zn(OH)2 )3 (ZnSO4 )(H2 O) n flakes at the initial assembly process due to the spontaneous formation of the electrostatic field in the primary battery.